Effect of Variations in Velocity Air Intake Cyclone Dimensions on Motorcycle Torque and Power - Ichsan Nasution; Wawan Purwanto; Budi Utomo Wisesa; Masykur Masykur (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2023)
The Velocity Air Intake System is an important component in a motor vehicle engine, particularly in a 155cc engine. Its function is to optimize the airflow process to the throttle body or carburetor. However, many users or people tend to overlook the significance of improving engine performance by varying the model or replacing the velocity air intake system itself. One common issue is the diameter and shape of the airflow model, which can affect the power, torque, and exhaust emissions produced. Installing a velocity air intake system is one approach to achieve an efficient air delivery process into the combustion chamber. In our research conducted using a dyno test on a 155cc four-stroke engine, the results showed that using a 46 mm size yielded the highest power of 11.03 Hp and produced a torque of 12.39 N.m. Using a 47 mm size resulted in 11.02 Hp and decreased the torque to 12.28 N.m. With a 48 mm size, there was a decrease in power to 11.00 Hp and an increase in torque to 12.72 N.m, while using a 45 mm size led to a decrease in power to 10.09 Hp and produced a torque of 11.31 N.m.